2020
DOI: 10.1021/acs.joc.9b03255
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Addition of Carbon-Centered Radicals to Ynamides. A Regio- and Stereoselective Route to Persubstituted α-Iodo-enamides

Abstract: Rather surprisingly, C–C bond formation through “intermolecular” radical addition to internal ynamides has never been reported. Actually, ynamides are excellent acceptors for “electrophilic” carbon-centered radicals. These processes enable the introduction of functionalized alkyl chains at Cβ, groups that have not yet been introduced via the addition of organometallics. Radical carboiodination affords persubstituted α-iodo-enamides in moderate to high yield. The addition is totally stereoselective. Theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In most cases, coupling reactions conducted with α-chloro-, α-bromo-, and α-iodoenamides gave trisubstituted or tetrasubstituted enamides with good to excellent yields with retention of the initial geometry of the double bond. 6 9 10 16 18 , 31 32 33 34 35 36 , 38 Isomerization of the double bond during these processes have been reported by Sahoo­, 20 Hammond and Xu, 13 and Tang. 5 They described the coupling reactions of ( E )-α-haloenamide to give a mixture of ( E )- and ( Z )-enamides due to partial isomerization that probably occurs during the palladium-catalyzed transformations.…”
Section: Transformations Of α-Haloenamidesmentioning
confidence: 85%
See 1 more Smart Citation
“…In most cases, coupling reactions conducted with α-chloro-, α-bromo-, and α-iodoenamides gave trisubstituted or tetrasubstituted enamides with good to excellent yields with retention of the initial geometry of the double bond. 6 9 10 16 18 , 31 32 33 34 35 36 , 38 Isomerization of the double bond during these processes have been reported by Sahoo­, 20 Hammond and Xu, 13 and Tang. 5 They described the coupling reactions of ( E )-α-haloenamide to give a mixture of ( E )- and ( Z )-enamides due to partial isomerization that probably occurs during the palladium-catalyzed transformations.…”
Section: Transformations Of α-Haloenamidesmentioning
confidence: 85%
“…In 2020 our group showed that the intermolecular addition of electrophilic carbon-centered radicals to ynamides using ATRA methodology afforded a new regio- and stereoselective route to persubstituted α-iodoenamides. 31 The addition of ethyl α-iodoacetate, α-iodoacetonitrile, or α-iodo- N , N -diethylacetamide onto ynamides derived from oxazolidinone and N -tosylbenzylamine was initiated with triethylborane in DCM. The reactions proceeded with total regio- and stereoselectivity to give α-iodoenamides in moderate to good yields (Scheme 37 ).…”
Section: α-Haloenamide Synthesismentioning
confidence: 99%
“…The direct addition of a carbon-centered radical onto ynamides 62 was recently investigated by the group of Bertrand and Feray, using an iodine atom transfer radical addition with α-iodo-esters, -amide and -nitrile (Scheme 24). [33] The tetrasusbtituted enamides 64 are obtained with good to excellent yields and perfect regio-and diastereo-selectivities. The initiation step with triethylborane and dioxygen would lead to the formation of the carbonyl-stabilized radical, which would add onto the ynamide (Scheme 25).…”
Section: Addition Of Carbon Centered Radicalsmentioning
confidence: 99%
“…The direct addition of a carbon‐centered radical onto ynamides 62 was recently investigated by the group of Bertrand and Feray, using an iodine atom transfer radical addition with α‐iodo‐esters, ‐amide and –nitrile (Scheme 24). [33] …”
Section: Intermolecular Addition Of Radicals On the Alkyne Moietymentioning
confidence: 99%
“…Very recently, Feray, Bertrand, and co‐workers demonstrated that with α‐iodoacetate as the radical precursor, ynamides 48 could undergo an intermolecular radical addition to synthesize persubstituted α‐iodo‐enamides in moderate to high yield with excellent regio‐ and stereoselectivity ( Scheme ). [ 23 ] Of note, this radical carboiodination represents the first example of the addition of intermolecular carbon centered radicals to ynamides. DFT calculations indicated that radical attack at the β‐position of ynamides is clearly favored over addition to α‐position of ynamides.…”
Section: β‐Additionmentioning
confidence: 99%